Everything is relevant : writings on art and life 1991-2018 - Lum, Ken, 1956- (Text/context : writings by Canadian artists, 2020)
"Everything is Relevant: Writings on Art and Life, 1991-2018 brings together texts by Canadian artist Ken Lum. They include a letter to an editor, diary entries, articles, catalogue essays, curatorial statements, and more. Along the way, the reader learns about late modern, postmodern, and contemporary art practices, as well as debates around issues like race, class, and monumentality. Penetrating, insightful, and often moving, Lum's writings are essential for understanding his practice, which has been prescient of developments within contemporary art, as well as the international art world over the last three decades."--